Posterior capsule opacification: pathology, clinical evaluation, and current means of prevention - Auffarth, Gerd U.; Peng, Qun (Ophthalmic practice, 2000)
Fifty years after the first implantation of an Intraocular Lens (IOL) by Harold Ridley, cataract surgery has become one of the most frequent and most successful surgical procedures performed in medicine. Even though tremendous advances have been made, especially during the last 10 to 15 years, in terms of surgical techniques and improvement of implant technology, posterior capsule opacification (PCO) still remains as the most common and serious long-term complication after cataract extraction and IOL implantation. New methods for quantitative, objective evaluation of secondary cataract formation, as well as clinical and laboratory (especially autopsy eyes) studies have significantly improved our understanding on how IOL design and material influence PCO. Sharp edge optic designs of IOLs of various materials have been shown to significantly reduce secondary cataract. Other means to enhance the mechanical barrier effect of an implant, such as special intracapsular bending rings, are now explored. Major advances in other areas of biotechnology and immunology, including gene therapeutical methods, offer totally new approaches for the future in the elimination of lens epithelium cells from the capsular bag. This survey gives an update on the pathology of PCO and influencing factors, as well as current and future means and trends to reduce or prevent PCO formation. In addition special reference is given to PCO evaluation methods.